2013
DOI: 10.5012/bkcs.2013.34.8.2271
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Titania Films with Ordered Nanopores and Their Application to Visible Light Water Splitting

Abstract: We report on the photoelectrochemical properties of partially reduced mesoporous titania thin films. The fabrication is achieved by synthesizing mesoporous titania thin films through the self-assembly of a titania precursor and a block copolymer, followed by aging and calcination, and heat-treatment under a H 2 (1 torr) environment. Depending on the temperature used for the reaction with H 2 , the degree of the reduction (generation of oxygen vacancies) of the titania is controlled. The oxygen vacancies induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This capacitance enhancement was attributed to the nanoporous architecture which provides easy access of the surface to liquid electrolyte, more active sites for ion binding and charge separation, and improvement in electrical conductivity. Muhammad et al reported reduced mp-TiO 2 thin films prepared by evaporation induced self-assembly using F127 as a pore template followed by heat treatment under a hydrogen environment [198]. The transparent titania thin films turned black upon heat treatment.…”
Section: Hydrogenationmentioning
confidence: 99%
“…This capacitance enhancement was attributed to the nanoporous architecture which provides easy access of the surface to liquid electrolyte, more active sites for ion binding and charge separation, and improvement in electrical conductivity. Muhammad et al reported reduced mp-TiO 2 thin films prepared by evaporation induced self-assembly using F127 as a pore template followed by heat treatment under a hydrogen environment [198]. The transparent titania thin films turned black upon heat treatment.…”
Section: Hydrogenationmentioning
confidence: 99%
“…Very recently, reduced titania with oxygen vacancies has also attracted researcher attention for its increased visible light absorption and conductivity. 12,13 It is known that the size of TNPs significantly affects all the properties of TNPs, including specific surface area, life-time of the electron-hole pair, conductivity, and so on. 14 The sol-gel method was investigated to control the size of TNPs because of its simple, inexpensive, and low temperature characteristics; titanium alkoxides are typical starting materials in the sol-gel method for hydrolysis and condensation to produce TNPs.…”
mentioning
confidence: 99%